Retrospective case control study on typhoid and non-typhoid small bowel perforation - Mahapatra, Sandeep; Panda, Charan (International Journal of Research in Medical Sciences, 2016)
Background: Out of several causes of small bowel perforations, Typhoid is the commonest cause in tropical countries claiming a higher morbidity and mortality profile. In Spite of conducting a good clinical examination and a battery of investigatory procedures, the etiology of perforation still remains obscure in a good number of cases. This retrospective case control study was conducted with an objective to evaluate the causes of small bowel perforation and to compare the surgical procedures and the outcomes in patients of typhoid and non-typhoid small bowel perforations. Methods: This study was based on hospital records for the last 3 years from April 2003 to April 2006. All the cases that were admitted with perforations had undergone a battery of tests to rule out the causes. 69 patients had one or the other test positive for typhoid (cases); the other causes of perforation were taken as control (n=43). Results: In typhoid perforations, although none of the operative procedures are clearly advantageous over the other, but anastomoses including the by-pass procedures are associated with more of complications wound dehiscence (p value 0.004), anastomotic leakage (p value 0.04), intra-abdominal collections (p value 0.009) with a longer hospital stay and hence to be avoided as practicable. Conclusions: Typhoid ileal perforation still has a poor prognosis with high morbidity and mortality. Late presentation, delayed surgery, multiple perforations, severe peritoneal contamination, and post-operative faecal fistula are factors that have an adverse effect on mortality. Most deaths occur during the early post-operative period, with survivors having a prolonged hospital stay.